LGICdb: the ligand-gated ion channel database - Le Novère, Nicolas (Oxford University Press, 2001)
Ligand-Gated Ion Channels (LGIC) are polymeric transmembrane proteins involved in the fast response to numerous neurotransmitters. All these receptors are formed by homologous subunits and the last two decades revealed an unexpected wealth of genes coding for these subunits. The Ligand-Gated Ion Channel database (LGICdb) has been developed to handle this increasing amount of data. The database aims to provide only one entry for each gene, containing annotated nucleic acid and protein sequences. The repository is carefully structured and the entries can be retrieved by various criteria. In addition to the sequences, the LGICdb provides multiple sequence alignments, phylogenetic analyses and atomic coordinates when available. The database is accessible via the World Wide Web (http://www.pasteur.fr/recherche/banques/LGIC/LGIC.html), where it is continuously updated. The version 16 (September 2000) available for download contained 333 entries covering 34 species.